Analisis Risiko dan Strategi Peningkatan Keselamatan Kerja di Sektor Industri Manufaktur: Tinjauan Literatur - Intifada, Winda S. (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Workplace safety in the manufacturing sector is a critical issue, given the high incidence of workplace accidents that may hurt the company and the workers. This study was conducted to analyze occupational safety risks and strategies for improvement, with a focus on the challenges faced in implementing safety policies that are often suboptimal. This research is a literature review employing a descriptive approach, where data from various secondary sources such as academic journals, reports, and official publications are systematically analyzed. The findings of the study indicate four main categories of occupational safety risks in the industrial sector: physical, chemical, ergonomic, and psychosocial risks. The application of technologies, such as automation and monitoring sensors based on the Internet of Things (IoT), has proven effective in reducing workplace accidents, but access to these technologies remains limited. Additional challenges include cost limitations, low worker awareness, weak safety culture implementation, and suboptimal enforcement of safety regulations. This study recommends the importance of collaboration between governments, companies, and workers to strengthen safety culture through investment in technology, ongoing training, and more rigorous regulation enforcement. With these measures, workplace safety in the industrial sector is expected to improve significantly and sustainably. Keywords: industrial risk, occupational safety, regulation, safety strategy